Bank Information Production Over the Business Cycle - Howes, Cooper; Weitzner, Gregory (Review of Economic Studies, 2025)
Abstract The information banks produce drives their lending decisions and macroeconomic outcomes, but this information is inherently difficult to analyse because it is private. We construct a novel measure of bank information quality from confidential regulatory data that include banks’ private risk assessments for US corporate loans. Information quality improves as local economic conditions deteriorate, particularly for new loans, large loans, and loans with higher expected losses. Information quality also declines during periods of rapid local house price appreciation. Our results provide empirical support for theories of countercyclical information production in credit markets.